THE FIRE ARCHETYPE IN DARIA MELNYKOVYCH-RYHYTSKA’S LYRICS - Машталер, О. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of interpretation of the fire archetype in Daria Ryhtytska’s lyrics. The specifics of the writer’s artistic thinkings, based on the dialectical embodiment of this archetype.